Mammaglobin A, a novel marker of minimal residual disease in early stages breast cancer - Janku, F; Kleibl, Z; Novotny, J; Tesarova, P; Petruzelka, L; Matous, B (Neoplasma, 2004)
Mammaglobin A, in contrast to other factors, is a breast specific member of uteroglobin gene family. Expression is restricted to normal and neoplastic breast epithelium. A highly homologous mammaglobin B is not specific to breast tissue. In this pilot feasibility study we examined expression of both markers for minimal residual disease in the bone marrow of patients with breast cancer. We obtained bone marrow aspirates of 34 patients with stage I (41%), II (56%) and III (3%) breast cancer who underwent either immediate complete resection of the tumor or neoadjuvant therapy with subsequent curative surgery. mRNA was isolated using QIAamp RNA blood mini kit (Qiagen). Subsequently two-step nested RT-PCR for the expression of mammaglobin A and mammaglobin B was performed. Mammaglobin A was detected in samples from 4 (12%) out of 34 patients. None of the specimens was positive for mammaglobin B. With a median follow-up of 21 month we observed only 2 recurrences, one in patient with mammaglobin A positive bone marrow.RT-PCR assay for mammaglobin A may be a useful tool for detection of occult breast cancer cells in the bone marrow. Clinical and prognostic relevance of minimal residual disease should be further investigated.
Keywords: senioři; Neoplasm Proteins; reziduální nádor; Breast Neoplasms; nádorové proteiny; Prognosis; Middle Aged; Neoplasm, Residual; Sensitivity and Specificity; nádory kostní dřeně; Adult; uteroglobin; mammaglobin A; Biomarkers, Tumor; polymerázová řetězová reakce s reverzní transkripcí; Neoplasm Staging; ženské pohlaví; nádorové biomarkery; prognóza; Humans; lidé středního věku; Uteroglobin; senzitivita a specificita; nádory prsu; staging nádorů; Reverse Transcriptase Polymerase Chain Reaction; dospělí; Female; Aged; Bone Marrow Neoplasms; Mammaglobin A; lidé